In vitro and in vivo investigations of selected varieties of Areca catechu L - Phytochemical analysis, antiulcer, and wound healing activity - R. Deveswaran; D.J. Madhu Kumar; V. Madhavan; Soma Chaki; Misbah Khan; Govind R. Kadambi; B.V. Basavaraj; J. Anbu (Phytomedicine Plus)
Background: This study investigated the phytochemical composition and potential medicinal properties of arecanut grown in various regions of Karnataka. Arecanut, commonly chewed in the Indian subcontinent and Southeast Asia for its purported medicinal benefits, contains arecoline, a pyridine alkaloid known for its pharmacological effects. Methods: Selected varieties of arecanut were subjected to phytochemical analysis, GC-MS, HPTLC analysis, cell line studies using human oral and intestinal cell lines, wound healing, and anti-ulcer activity studies. Results: Phytochemical analysis of the selected arecanut revealed the presence of various compounds including alkaloids, phytosterols, fixed oils, saponins, and phenolic compounds. Further analysis through GC-MS of alcoholic and aqueous extracts identified 11 phytochemical constituents. High-performance thin Layer Chromatography (HPTLC) was employed to quantify the percentage of arecoline, ranging from 0.12 % to 0.95 % in the samples. Cell line studies using human gingival fibroblasts demonstrated that higher doses of the extracts exhibited a mitogenic effect, with a plateau observed at higher concentrations. Lower concentrations showed maximum cell viability, reaching 80 % at 2.5 mg/mL. These findings suggest a potential pro-fibrotic effect of the extracts. The study evaluated the wound healing activity of arecanut extracts. Treatment with arecagel resulted in a significant reduction in wound area compared to control and standard groups, indicating its potential in wound healing applications. In ulcer healing, the study utilized a pyloric ligation model, revealing the effectiveness of arecanut extract in promoting the healing of stomach ulcers. Overall, this research provides valuable insights into the phytochemical composition and medicinal properties of arecanuts from different regions of Karnataka. Conclusion: The findings could be beneficial for farmers in selecting suitable arecanut varieties for cultivation, and the identified medicinal properties may have implications among the farmer's community.